Factors Affecting the Job Performance of Employees in the Construction Industry Group of a Company in Bangkok - ฮะวังจู, กฤตเมธ; เมืองแก่น, เสาวภา; แย้มชุติ, คณบดี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this study were (1) study the internal organizational factors affecting the job performance of employees in the construction industry. (2) study the motivational factors influencing job performance in the construction industry. (3) study the level of job performance among employees as influenced by internal organizational factors and work motivation, and        (4) study the internal organizational factors and motivational factors that affect job performance efficiency of employees in the construction industry of a company in Bangkok.          The population consists of employees in the construction industry of a company in Bangkok, totaling 187 people. The research instrument used was a questionnaire with an overall reliability coefficient of 0.979. The statistics used for data analysis included frequency, percentage, mean, standard deviation, and multiple regression analysis.          The results revealed that the internal organizational factor with the highest mean score was organizational structure (  = 4.43). For motivational factors, the highest mean score was found in the aspect of achievement (  = 4.62). Regarding job performance, the quality aspect had the highest mean score (  = 4.48). The analysis of the relationship between internal organizational factors and work motivation indicated that the organizational structure, along with motivational factors such as achievement and responsibility, had a statistically significant effect on employee job performance at the 0.05 level.